Association between perinatal factors and hypospadias in newborns: a retrospective case-control study of 42,244 male infants - Yi Wang; Lin Wang; Zeyong Yang; Fang Chen; Zhiwei Liu; Zheng Tang (BMC, 2022)
Abstract Background Hypospadias is one of the most common male congenital malformations worldwide. It is characterised by the abnormal positioning of the opening of urethra, and may lead to problems with urination and sexual function. Various factors were suggested to contribute to hypospadias pathogen. This study aimed to evaluate the relationship between perinatal factors and neonatal hypospadias based on a large sample of male newborns. Methods This retrospective case-control study was conducted at the International Peace Maternal and Child Health Hospital, Shanghai Jiao Tong University School of Medicine. Male infants with hypospadias (N = 97) and without any birth defects (N = 42,147) who were born in January 2015 to December 2019 were enrolled in this study. A statistical analysis of perinatal factors, such as maternal age, primiparity, multiple births, hypertensive disorders of pregnancy (HDP), diabetes mellitus (DM), placenta previa, thyroid diseases, hepatitis B, obesity, meconium-stained amniotic fluid, gestational age, low birth weight (LBW), small for gestational age (SGA) and in vitro fertilization (IVF) was used to assess the risk factors for hypospadias. Results The overall incidence of hypospadias in male infants was 0.23% (97/42,244). The univariate analysis of potential risk factors for hypospadias showed that HDP, primiparity, multiple births, hyperthyroidism, preterm delivery, LBW and SGA had a statistical association with hypospadias. After adjusting for potential confounders in a multivariate regression analysis, the odds ratios (OR) and 95% confidence intervals (CI) were calculated for the following risk factors for hypospadias: HDP (OR: 3.965, 95% CI: 2.473-6.359, P <  0.01), multiple births (OR: 2.607, 95% CI: 1.505-4. 514, P <  0.01) and hyperthyroidism (OR:4.792, 95% CI: 1.700-13.506, P <  0.01), which suggested these factors were significant independent risk factors for hypospadias. Conclusions Perinatal factors, such as HDP, multiple births and hyperthyroidism may be associated with hypospadias in male infants.